Elevation-gradient patterns of soil microaggregate elemental distribution and chemical morphology in Tongbai Mountain, China’s North–South climatic transition zone - Li, Chunjie; Guo, Shili (Frontiers in Environmental Science, 2025)
Mountain-soil microaggregates play a crucial role in carbon storage and the transport of heavy metals. However, their biogeochemical behavior along elevation gradients is not well understood. In this study, we examine the chemistry of microaggregates from 200 m to 1,140 m on Tongbai Mountain, located in Central China. We employ a range of surface- and bulk-sensitive techniques, including X-ray photoelectron spectroscopy, scanning electron microscopy with energy-dispersive spectroscopy, X-ray fluorescence, Fourier-transform infrared spectroscopy, and X-ray diffraction. Our analysis reveals three distinct altitudinal regimes in elemental distribution. At low elevations (<600 m), microaggregate surfaces are enriched in Mn and Fe (XPS Mn up to 1.61% and Fe ≈ 3.37% at 200 m), reflecting exogenous inputs and reducing conditions that favour metal mobility. Mid-elevations soils (600–700 m) host elevated P and Al, signalling intense weathering and biological turnover in this transition zone. Above 700 m, cooler and wetter conditions promote the formation of organo-mineral complexes that sequester C, N and Fe; the C-N component in XPS spectra rises from 19.2% at 200 m to 26.4% at 1,140 m, while pyridinic-N increases from 21.1% to 44.4%. Concurrently, Fe3+ becomes the dominant iron species, consistent with enhanced humification and oxidative weathering at higher elevations. These trends point to an altitudinal threshold near 600–700 m. Below this break point, weaker organo-mineral associations allow greater heavy-metal mobility and carbon loss. Above it, robust complexes act as sinks for both carbon and metals, buffering soils against disturbance. Management should therefore be stratified: stringent pollution controls at low elevations, vegetation reinforcement on mid-slopes and conservation of high-elevation refugia. Our findings provide a mechanistic framework for mountain soil stewardship under global change. Projected warming and altered precipitation are likely to intensify metal leaching at lower elevations while underscoring the role of high-elevation soils as critical reservoirs for carbon and metal retention within China’s north–south climatic transition zone.